Determinasi Tax Avoidance - Afifah Ayu Cahyaningrum; Sartika Wulandari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tax avoidance is an effort by taxpayer to reduce tax expense by not violating the tax laws or other rules in force. However, in fact tax avoidance is something that is not wanted by the government so the government created the rules to prevent it. This study aimed to examine the effect of Good Corporate Governance (Board of Commissioners, Audit Committee, Independent Board of Commissioners, Institutional Ownership), Profitability, Capital Intensity, Firm Size To the Tax Avoidance of the Technology, Healthcare, Consumer Non-Cyclical and Industrials sector companies listed on the Indonesia Stock Exchange (BEI) with a 3 year observation period in 2020-2022. The theory used in this study was agency theory. The number of observations is 300 samples obtained by the nonprobability sampling method, and purposive sampling technique. The analysis technique used in this research is multiple linear regression analysis. The results of this research show that the Board of Commissioners, Audit Committee, Independent Board of Commissioners, Institutional Ownership, Audit Committee and Company Size do not affect tax avoidance. Meanwhile, Profitability and Capital Intensity affect tax avoidance.